Glycemic index diet for dummies - Raffetto, Meri (For dummies, 2014)
Eating fewer carbohydrates may be trendy-- but since your body needs them to function, eliminating too many carbs from your diet is neither healthy nor practical. Learn the glycemic index system to help you shed unwanted pounds and improve your overall health.--Source other than Library of Congress.